The effect of text and graphic cue-based action observation on the working memory performance of novice badminton players - Dukchan Jang; Junho Ha (Frontiers in Psychology)
IntroductionUnderstanding strategic situations is essential in sports. There has been relatively little research examining the effectiveness of action observation based on visual cues in strategic situations. This study investigated whether action observation with visual cues can help performers understand the strategic aspects of complex sports by analyzing the effect of text cue-based action observation and graphic cue-based action observation on the accuracy and speed of cognitive information processing in working memory.MethodsForty-four male and female novice badminton players participated in the experiment. They were randomly assigned to one of four groups: text cue-based action observation (TAO), graphic cue-based action observation (GAO), action observation (AO), and a control group (CON). The experimental design consisted of a pre-test, intervention, and post-test. The experiment analyzed the accuracy and response time of cognitive information processing in working memory.ResultsThe accuracy and response time analysis showed that the AO group significantly improved their cognitive performance accuracy and response time from pre-test to post-test compared to the control group. The TAO and GAO groups with visual cues significantly outperformed the AO and CON groups for accuracy. However, only the TAO group significantly outperformed the other groups in term of response time. The GAO group improved significantly compared to the CON group but not significantly compared to the AO.ConclusionThese results suggest that visual cues can influence the modulation of cognitive load in working memory and that TAO is a relatively more efficient perceptual-cognitive training method for novices.